Anti-corrosion artificial stone plate doped with tailings and preparation method of anti-corrosion artificial stone plate
Through high -voltage pressure and curing technology, the doped slate of quartz sand, tailings and resins is prepared to solve the problem of easy corruption of existing anticorrosive materials and achieve the effect of high pressure, acid resistance and tailings resource use. Essence
Patent Information
- Application Number
- CN202411471316.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
Existing anticorrosion materials are prone to cracks, corrosion, hollowing, lifting, sinking and other problems during use, resulting in high maintenance costs, short service life, and failure to effectively utilize tailings resources.
Materials such as quartz sand, tail mine powder, resin and other materials are used to prepare artificial slate with high density, low water absorption rate, and acid -resistant corrosion of acid and corrosion through high -pressure suppression, solidification, polishing, and cutting edges.
It achieves higher pressure resistance and acid corrosion resistance, extends the service life, utilizes tailings resources, and reduces environmental risks and maintenance costs.
Smart Images

Figure CN119349926A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of artificial stone, and in particular relates to an anti-corrosion artificial stone plate doped with tailings and a preparation method thereof. Background Art
[0002] At present, pressure-resistant anti-corrosion materials are needed on the ground of smelters, chemical plants, national defense bases, etc. Commonly used materials are natural granite, acid-resistant tiles, resin mortar, furan concrete and other materials. These traditional anti-corrosion materials will show varying degrees of cracks, corrosion, hollowing, warping, and sinking after 2-3 years of use. They have high maintenance costs, short service life, and safety and environmental protection issues. Therefore, there is an urgent need for anti-corrosion materials with better performance.
[0003] Tailings are the particulate solid waste left after the original ore is crushed and beneficiated. At present, China's tailings storage is huge and is still growing. The large amount of tailings accumulation poses a certain risk to the ecological environment. How to realize the resource utilization of tailings is also a problem currently faced by mining companies.
[0004] In view of the above problems, the present invention provides an anti-corrosion artificial stone plate doped with tailings and a preparation method thereof. The present invention uses quartz sand, tailings powder and resin as main raw materials, and obtains an artificial stone plate with high density, low water absorption and acid corrosion resistance through high-pressure pressing, and then solidification, polishing and trimming, which can meet the demand for anti-corrosion materials in the fields of hydrometallurgy, chemical industry, electric power, environmental protection, etc. By adding tailings powder as powder, the resource utilization of tailings is realized, providing a new idea for the comprehensive utilization of tailings in mining enterprises. Summary of the invention
[0005] The purpose of the present invention is to provide an anti-corrosion artificial stone plate doped with tailings. Compared with traditional anti-corrosion materials such as acid-resistant tiles, granite, resin mortar, furan concrete, etc., the artificial stone plate provided by the present invention is more pressure-resistant and acid-resistant, has a longer service life, and can also realize the resource utilization of tailings.
[0006] In order to achieve the above technical problems, the technical solution of the present invention is: an anti-corrosion artificial stone plate doped with tailings, the anti-corrosion artificial stone plate comprising the following raw materials in parts by weight: 40-70 parts of quartz sand, 20-50 parts of tailings powder, 5-12 parts of resin, 0.05-0.25 parts of coupling agent, 0.1-0.2 parts of curing agent, and 0.02-0.05 parts of accelerator.
[0007] Furthermore, the quartz sand is one or more of 4-6 mesh quartz sand, 8-16 mesh quartz sand, and 40-70 mesh quartz sand.
[0008] Furthermore, the tailings powder is one or more of copper, lead, zinc, gold and iron tailings.
[0009] Furthermore, the resin is a corrosion-resistant epoxy resin.
[0010] Furthermore, the curing agent is one or more of methyl ethyl ketone peroxide, cumene hydroperoxide, xylene peroxide, tert-butyl peroxy-2-ethylhexanoate, and tert-butyl benzoyl peroxide.
[0011] Furthermore, the coupling agent is one or more of a silane coupling agent, an aluminate coupling agent, a titanate coupling agent, a phosphate coupling agent, a zirconate coupling agent, and a stannate coupling agent.
[0012] Furthermore, the promoter is one or more of cobalt cyclohexaneate, cobalt isooctanoate, potassium isooctanoate, copper isooctanoate, calcium isooctanoate, sodium isooctanoate, zinc isooctanoate and the like.
[0013] Another object of the present invention is to provide a method for preparing the above-mentioned anti-corrosion artificial stone plate doped with tailings, the method comprising the following steps:
[0014] (1) Raw material preparation
[0015] Weigh each material according to the designed ratio, first add quartz sand and tailings powder into the planetary mixer, stir for 2 to 5 minutes to obtain solid material; then add resin, coupling agent, curing agent and accelerator into the color paste disperser, stir for 2 to 5 minutes to obtain liquid material;
[0016] Add the liquid material into the planetary agitator filled with solid material, stir for 5 to 10 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material;
[0017] Place a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold, then place a circle of EVA sponge strips around the inside of the mold. The strips are 10-50mm wide and 5-10mm higher than the mold. Place the pressed sheet material evenly on the mold, and then place another piece of kraft paper on it.
[0018] (2) Molding
[0019] Send the mold with fabric to the hydraulic press, set the pressing pressure and pressing time, put down the pressing plate, and press the mold with a pressure of 30-100MPa and a pressing time of 30-60 seconds;
[0020] De-mould the pressed sample, and then heat and cure the demoulded plate in an oven for 30 to 120 minutes at a temperature of 60 to 100°C.
[0021] (3) Processing
[0022] The solidified board is placed in a thickness gauge for sizing, and then sent to a polishing machine for polishing. The polished board is then trimmed to obtain the final artificial stone board.
[0023] Furthermore, the thickness of the artificial stone plate is 8-30 mm, and the density is not less than 2.41 g / cm 3 , water absorption rate is as low as 0.011%.
[0024] The beneficial effects of the present invention are as follows: under the condition of relatively low resin addition amount, the present invention compacts quartz sand, tailings and resin by formula optimization and high-pressure pressing to obtain a high-strength anti-corrosion artificial stone plate with high density and extremely low water absorption; and by adding tailings, the resource utilization of tailings is realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram comparing the surface morphology of the artificial stone plate of the present invention before and after being soaked in 30% sulfuric acid. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0027] The invention discloses an anticorrosive artificial stone plate doped with tailings, which comprises the following raw materials in parts by weight: 40-70 parts of quartz sand, 20-50 parts of tailings powder, 5-12 parts of resin, 0.05-0.25 parts of coupling agent, 0.1-0.2 parts of curing agent and 0.02-0.05 parts of accelerator.
[0028] Preferably, the quartz sand comprises: 10-30 parts of 4-6 mesh quartz sand, 10-30 parts of 8-16 mesh quartz sand, 10-20 parts of 40-70 mesh quartz sand, with a silicon content of >99% and a water content of less than 0.1%.
[0029] Preferably, the tailings powder is copper tailings powder, the water content in the tailings is less than 0.1%, the acid (50% sulfuric acid) soluble content is not higher than 5%, and it can pass through a 100-mesh sieve.
[0030] Preferably, the resin is a general-purpose bisphenol A epoxy vinyl ester resin, the curing agent is methyl ethyl ketone peroxide, the coupling agent is a silane coupling agent, and the accelerator is cobalt cyclohexaneate.
[0031] Preferably, the thickness of the artificial stone plate is 20 mm.
[0032] Preferably, the size of the artificial stone slab is 200mm*200mm, 200mm*300mm, 300mm*300mm, 300mm*400mm, 400mm*400mm, 400mm*600mm, depending on customer needs.
[0033] The method for preparing the anti-corrosion artificial stone plate doped with tailings comprises the following preparation steps:
[0034] (1) Raw material preparation
[0035] ① Ingredients: Add quartz sand and tailings powder into a planetary mixer according to the formula, stir for 2 to 5 minutes to obtain a solid material; add resin, coupling agent, curing agent and accelerator into a color paste disperser according to the formula, stir for 2 to 5 minutes to obtain a liquid material.
[0036] ② Stirring: Add the liquid material into the planetary agitator filled with solid material, stir for 5 to 10 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material.
[0037] ③ Fabric: Lay a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold, then lay a circle of EVA sponge strips around the inside of the mold. The strips are 10 to 50 mm wide and 5 to 10 mm higher than the mold. Spread the pressed sheet material evenly on the mold to make it as flat as possible, and then lay another piece of kraft paper on it.
[0038] (2) Molding
[0039] ① Pressing: Send the mold with fabric to the press, set the pressing pressure and pressing time, put down the pressing plate, and apply pressure to the mold. The pressure is 30-100MPa and the pressing time is 30-60 seconds.
[0040] ② Heat curing: demould the pressed sample, and then place the demoulded plate in an oven for heating and curing. The curing time is 30 to 120 minutes and the curing temperature is 60 to 100°C.
[0041] (3) Processing
[0042] ① Thickness determination: Place the solidified sheet in a thickness determination machine to determine the thickness, with a thickness of 8 to 30 mm.
[0043] ②Polishing: Then send the plate into the polishing machine for polishing.
[0044] ③ Trimming: Trim the slabs with a certain thickness to obtain the final artificial stone slabs.
[0045] Preferably, in the method for preparing the anti-corrosion artificial stone plate doped with tailings, the pressing pressure is 50-80 MPa and the pressing time is 40-50 seconds.
[0046] Preferably, in the method for preparing the anti-corrosion artificial stone plate doped with tailings, the curing time is 90-120 minutes and the curing temperature is 70-90°C.
[0047] Example 1
[0048] (1) Raw material preparation
[0049] ① Ingredients: Add 30 parts of 4-6 mesh quartz sand, 18 parts of 8-16 mesh quartz sand, 5 parts of 40-70 mesh quartz sand, and 40 parts of tailings into a planetary mixer and stir for 5 minutes to obtain a solid material; add 7 parts of resin, 0.11 parts of curing agent, 0.11 parts of coupling agent, and 0.01 parts of accelerator into a disperser and stir at a speed of 100 rpm for 2 minutes to obtain a liquid material.
[0050] ② Stirring: Add the liquid material into the planetary stirrer filled with solid material and stir for 8 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material.
[0051] ③ Fabric: Lay a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold (size 300mm*300mm, depth 20mm), then lay a circle of EVA sponge strips around the inside of the mold, the width of the strip is 30mm, spread the pressboard material evenly on the mold to make it as flat as possible, and then lay another piece of kraft paper.
[0052] (2) Molding
[0053] ① Pressing: Send the mold with the fabric to the press, set the pressing pressure and pressing time, put down the pressing plate, and press the mold with a pressure of 50MPa and a pressing time of 60 seconds.
[0054] ② Heat curing: demould the pressed sample, and then place the demoulded plate in an oven for heating and curing. The curing time is 120 minutes and the curing temperature is 80℃.
[0055] (3) Processing
[0056] ① Thickness determination: Place the solidified sheet in a thickness determination machine to determine the thickness, the thickness is 20mm.
[0057] ②Polishing: Then send the plate into the polishing machine for polishing.
[0058] ③ Trimming: Trim the slabs with a certain thickness to obtain the final artificial stone slabs.
[0059] Example 2
[0060] (1) Raw material preparation
[0061] ① Ingredients: Add 30 parts of 4-6 mesh quartz sand, 23 parts of 8-16 mesh quartz sand, 10 parts of 40-70 mesh quartz sand, and 30 parts of tailings into a planetary mixer and stir for 5 minutes to obtain a solid material; add 7 parts of resin, 0.11 parts of curing agent, 0.11 parts of coupling agent, and 0.01 parts of accelerator into a disperser and stir at a speed of 100 rpm for 2 minutes to obtain a liquid material.
[0062] ② Stirring: Add the liquid material into the planetary stirrer filled with solid material and stir for 8 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material.
[0063] ③ Fabric: Lay a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold (size 300mm*300mm, depth 20mm), then lay a circle of EVA sponge strips around the inside of the mold, the width of the strip is 30mm, spread the pressboard material evenly on the mold to make it as flat as possible, and then lay another piece of kraft paper.
[0064] (2) Molding
[0065] ① Pressing: Send the mold with the fabric to the press, set the pressing pressure and pressing time, put down the pressing plate, and press the mold with a pressure of 50MPa and a pressing time of 60 seconds.
[0066] ② Heat curing: demould the pressed sample, and then place the demoulded plate in an oven for heating and curing. The curing time is 120 minutes and the curing temperature is 80℃.
[0067] (3) Processing
[0068] ① Thickness determination: Place the solidified sheet in a thickness determination machine to determine the thickness, the thickness is 20mm.
[0069] ②Polishing: Then send the plate into the polishing machine for polishing.
[0070] ③ Trimming: Trim the slabs with a certain thickness to obtain the final artificial stone slabs.
[0071] Example 3
[0072] (1) Raw material preparation
[0073] ① Ingredients: Add 30 parts of 4-6 mesh quartz sand, 28 parts of 8-16 mesh quartz sand, 10 parts of 40-70 mesh quartz sand, and 25 parts of tailings into a planetary mixer and stir for 5 minutes to obtain a solid material; add 7 parts of resin, 0.11 parts of curing agent, 0.11 parts of coupling agent, and 0.01 parts of accelerator into a disperser and stir at a speed of 100 rpm for 2 minutes to obtain a liquid material.
[0074] ② Stirring: Add the liquid material into the planetary stirrer filled with solid material and stir for 8 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material.
[0075] ③ Fabric: Lay a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold (size 300mm*300mm, depth 20mm), then lay a circle of EVA sponge strips around the inside of the mold, the width of the strip is 30mm, spread the pressboard material evenly on the mold to make it as flat as possible, and then lay another piece of kraft paper.
[0076] (2) Molding
[0077] ① Pressing: Send the mold with the fabric to the press, set the pressing pressure and pressing time, put down the pressing plate, and press the mold with a pressure of 50MPa and a pressing time of 60 seconds.
[0078] ② Heat curing: demould the pressed sample, and then place the demoulded plate in an oven for heating and curing. The curing time is 120 minutes and the curing temperature is 80℃.
[0079] (3) Processing
[0080] ① Thickness determination: Place the solidified sheet in a thickness determination machine to determine the thickness, the thickness is 20mm.
[0081] ②Polishing: Then send the plate into the polishing machine for polishing.
[0082] ③ Trimming: Trim the slabs with a certain thickness to obtain the final artificial stone slabs.
[0083] Example 4
[0084] (1) Raw material preparation
[0085] ① Ingredients: Add 30 parts of 4-6 mesh quartz sand, 23 parts of 8-16 mesh quartz sand, 10 parts of 40-70 mesh quartz sand, and 30 parts of tailings into a planetary mixer and stir for 5 minutes to obtain a solid material; add 7 parts of resin, 0.11 parts of curing agent, 0.11 parts of coupling agent, and 0.01 parts of accelerator into a disperser and stir at a speed of 100 rpm for 2 minutes to obtain a liquid material.
[0086] ② Stirring: Add the liquid material into the planetary stirrer filled with solid material and stir for 8 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material.
[0087] ③ Fabric: Lay a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold (size 300mm*300mm, depth 20mm), then lay a circle of EVA sponge strips around the inside of the mold, the width of the strip is 30mm, spread the pressboard material evenly on the mold to make it as flat as possible, and then lay another piece of kraft paper.
[0088] (2) Molding
[0089] ① Pressing: Send the mold with the fabric to the press, set the pressing pressure and pressing time, put down the pressing plate, and apply pressure to the mold. The pressure is 70MPa and the pressing time is 60 seconds.
[0090] ② Heat curing: demould the pressed sample, and then place the demoulded plate in an oven for heating and curing. The curing time is 120 minutes and the curing temperature is 80℃.
[0091] (3) Processing
[0092] ① Thickness determination: Place the solidified sheet in a thickness determination machine to determine the thickness, the thickness is 20mm.
[0093] ②Polishing: Then send the plate into the polishing machine for polishing.
[0094] ③ Trimming: Trim the slabs with a certain thickness to obtain the final artificial stone slabs.
[0095] Example 5
[0096] (1) Raw material preparation
[0097] ① Ingredients: Add 30 parts of 4-6 mesh quartz sand, 23 parts of 8-16 mesh quartz sand, 10 parts of 40-70 mesh quartz sand, and 30 parts of tailings into a planetary mixer and stir for 5 minutes to obtain a solid material; add 7 parts of resin, 0.11 parts of curing agent, 0.11 parts of coupling agent, and 0.01 parts of accelerator into a disperser and stir at a speed of 100 rpm for 2 minutes to obtain a liquid material.
[0098] ② Stirring: Add the liquid material into the planetary stirrer filled with solid material and stir for 8 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material.
[0099] ③ Fabric: Lay a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold (size 300mm*300mm, depth 20mm), then lay a circle of EVA sponge strips around the inside of the mold, the width of the strip is 30mm, spread the pressboard material evenly on the mold to make it as flat as possible, and then lay another piece of kraft paper.
[0100] (2) Molding
[0101] ① Pressing: Send the mold with the fabric to the press, set the pressing pressure and pressing time, put down the pressing plate, and press the mold with a pressure of 90MPa and a pressing time of 60 seconds.
[0102] ② Heat curing: demould the pressed sample, and then place the demoulded plate in an oven for heating and curing. The curing time is 120 minutes and the curing temperature is 80℃.
[0103] (3) Processing
[0104] ① Thickness determination: Place the solidified sheet in a thickness determination machine to determine the thickness, the thickness is 20mm.
[0105] ②Polishing: Then send the plate into the polishing machine for polishing.
[0106] ③ Trimming: Trim the slabs with a certain thickness to obtain the final artificial stone slabs.
[0107] Performance tests were performed on Examples 1-5, and the test items, test standards, and performance test results are shown in Table 1.
[0108] Table 1 Performance test results of Examples 1-5
[0109]
[0110]
[0111] The data in Table 1 show that the comprehensive performance of Example 4 is the best, with a board density of 2.35, a water absorption rate as low as 0.011%, a bending strength of 43.3 MPa, a compressive strength of 167.4 MPa, and a linear thermal expansion coefficient as low as 1.6×10 -5 ℃ -1 , impact strength reaches 4.7J, acid resistance reaches 99.5%. Comparison of Examples 1-3 shows that too much tailings will lead to insufficient compaction of the plate and poor performance. Comparison of Examples 2, 4, and 5 shows that the best pressing pressure is 70MPa. If the pressure is too low, the plate will not be compacted. If the pressure is too high, the quartz sand will be crushed, resulting in performance degradation.
[0112] In order to further test the acid resistance of the plate of Example 4, the plate was immersed in 30% sulfuric acid at room temperature for 30 days. Figure 1 Table 2 is the actual picture of the plate before and after immersion. Table 2 shows the bending strength and mass changes of the plate before and after immersion. Figure 1 The appearance of the board before and after immersion has no obvious change, and the results in Table 2 show that the bending strength of the board after immersion is only reduced by 0.9%, and the mass loss is 0.095%. It can be seen that the artificial stone board of the present invention exhibits excellent sulfuric acid corrosion resistance.
[0113] Table 2 Changes in bending strength and mass loss of plates after immersion in sulfuric acid
[0114] Flexural strength before immersion Flexural strength after immersion Reduced bending strength Quality reduction 43.3MPa 42.9MPa 0.9% 0.095%
[0115] In addition, the chemical resistance test method in JC / T 908-2013 was used to test the corrosion resistance of the artificial stone plate of the present invention to common acid solutions, and the test results are shown in Table 3. The results show that, except for hydrofluoric acid, the artificial stone plate of the present invention exhibits good corrosion resistance to common acids.
[0116] Table 3 Corrosion resistance of artificial stone panels to common acid solutions
[0117] Serial number Acid type Corrosion resistance 1 hydrochloric acid Resistance 2 Nitric acid≤40% Resistance 3 Acetic acid ≤40% Resistance 4 30% sulfuric acid, hydrochloric acid, nitric acid mixed solution of equal volume Resistance 5 Hydrofluoric acid Intolerance
[0118] It should be noted that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. An anti-corrosion artificial stone plate doped with tailings, characterized in that: The anti-corrosion artificial stone plate comprises the following raw materials in parts by weight: 40-70 parts of quartz sand, 20-50 parts of tailings powder, 5-12 parts of resin, 0.05-0.25 parts of coupling agent, 0.1-0.2 parts of curing agent, and 0.02-0.05 parts of accelerator.
2. The anti-corrosion artificial stone plate doped with tailings according to claim 1, characterized in that: The quartz sand is one or more of 4-6 mesh quartz sand, 8-16 mesh quartz sand, and 40-70 mesh quartz sand.
3. The anti-corrosion artificial stone plate doped with tailings according to claim 1, characterized in that: The tailings powder is one or more of copper, lead, zinc, gold and iron tailings.
4. The anti-corrosion artificial stone plate doped with tailings according to claim 1, characterized in that: The resin is a corrosion-resistant epoxy resin.
5. The anti-corrosion artificial stone plate doped with tailings according to claim 1, characterized in that: The curing agent is one or more of methyl ethyl ketone peroxide, cumene hydroperoxide, xylene peroxide, tert-butyl peroxy-2-ethylhexanoate, and tert-butyl benzoyl peroxide.
6. The anti-corrosion artificial stone plate doped with tailings according to claim 1, characterized in that: The coupling agent is one or more of a silane coupling agent, an aluminate coupling agent, a titanate coupling agent, a phosphate coupling agent, a zirconate coupling agent, and a stannate coupling agent.
7. The anti-corrosion artificial stone plate doped with tailings according to claim 1, characterized in that: The promoter is one or more of cobalt naphthenate, cobalt isooctanoate, potassium isooctanoate, copper isooctanoate, calcium isooctanoate, sodium isooctanoate and zinc isooctanoate.
8. A method for preparing an anti-corrosion artificial stone plate doped with tailings as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) Raw material preparation Weigh each material according to the designed ratio, first add quartz sand and tailings powder into the planetary mixer, stir for 2 to 5 minutes to obtain solid material; then add resin, coupling agent, curing agent and accelerator into the color paste disperser, stir for 2 to 5 minutes to obtain liquid material; Add the liquid material into the planetary agitator filled with solid material, stir for 5 to 10 minutes to mix the solid and liquid evenly to obtain the final pressed sheet material; Place a layer of high-strength kraft paper of the same specifications on the bottom of the prepared mold, then place a circle of EVA sponge strips around the inside of the mold. The strips are 10-50mm wide and 5-10mm higher than the mold. Place the pressed sheet material evenly on the mold, and then place another piece of kraft paper on it. (2) Molding Send the mold with fabric to the hydraulic press, set the pressing pressure and pressing time, put down the pressing plate, and press the mold with a pressure of 30-100MPa and a pressing time of 30-60 seconds; De-mould the pressed sample, and then heat and cure the demoulded plate in an oven for 30 to 120 minutes at a temperature of 60 to 100°C. (3) Processing The solidified board is placed in a thickness gauge for sizing, and then sent to a polishing machine for polishing. The polished board is then trimmed to obtain the final artificial stone board.
9. The method according to claim 8, characterized in that The thickness of the artificial stone plate is 8-30mm, and the density is not less than 2.41g / cm 3 , water absorption rate is as low as 0.011%.